The kingdom of the blind: disentangling fundamental drivers in the evolution of eye loss - Sumner-Rooney, L (Oxford University Press, 2018)
Light is a fundamentally important biological cue used by almost every animal on earth, to maintain daily rhythms, navigate, forage, find mates or avoid predators. But an enormous number of species live in darkness: in subterranean caves, deep oceans, underground burrows, and within parasitic host bodies, and the loss of eyes appears consistently across these ecosystems. However, the evolutionary mechanisms that lead to the reduction of the visual system remain the subject of great interest and debate more than 150 years after Darwin tackled the issue. Studies of model taxa have discovered significant roles for natural selection, neutral evolution and pleiotropy, but the interplay between them remains unclear. To nail down unifying concepts surrounding the evolution of eye loss, we must embrace the enormous range of affected animals and habitats. The fine developmental details of model systems such as the Mexican cave tetra Astyanax mexicanus have transformed and enriched the field, but these should be complemented by wider studies to identify truly overarching patterns that apply throughout animals. Here, the major evolutionary drivers are placed within a conceptual cost-benefit framework that incorporates the fundamental constraints and forces that influence evolution in the dark. Major physiological, ecological and environmental factors are considered within the context of this framework, which appears faithful to observed patterns in deep-sea and cavernicolous animals. To test evolutionary hypotheses, a comparative phylogenetic approach is recommended, with the goal of studying large groups exhibiting repeated reduction, and then comparing these across habitats, taxa, and lifestyles. Currently, developmental and physiological methods cannot feasibly be used on such large scales, but penetrative imaging techniques could provide detailed morphological data non-invasively and economically for large numbers of species. Comprehensive structural datasets can then be contextualised phylogenetically to examine recurrent trends and associations, and to reconstruct character histories through multiple independent transitions into darkness. By assessing these evolutionary trajectories within an energetic cost-benefit framework, the relationships between fundamental influences can be inferred and compared across different biological and physical parameters. However, substantial numbers of biological and environmental factors affect the evolutionary trajectory of loss, and it is critical that researchers make fair and reasonable comparisons between objectively similar groups.